Peran LAZ Sidogiri Dalam Memberdayakan Ekonomi Masyarakat Pasuruan Melalui Filantropi Islam - Syamsuri Syamsuri; Deliar Agha Firdaus Firdaus; Imam Kamaluddin Kamaluddin (Faculty of Economics and Management, 2020)
Poverty, economic inequality, and unemployment are common problems in economic empowerment in Indonesia. Poverty is the main problem in community economic empowerment because poverty will impact economic inequality and unemployment. Economic disparities were generating by an imbalance in income distribution between high-income and low-income groups. Poverty is a problem, a trial, and can even be a dangerous disaster that harms individuals and society. One means that Islam demands Muslims to eradicate poverty is through zakat institutions, which are an integral part of Islam’s pillars. This study aims to determine the role of the Sidogiri Amil Zakat Institution (LAZ) in empowering the community’s economy and find out the obstacles and solutions faced bythe Sidogiri LAZ in empowering the community’s economy. This research is qualitative. The type of research uses descriptive analysis, namely, in the form of written data by re-describing the research object’s data. This study indicates that the Sidogiri LAZ has a community economic empowerment program run based on the care of the Sidogiri LAZ to improve the community’s economy through business skills training and business capital assistance to the community, such as business capital assistance. Poor communities, training and improving human resources in entrepreneurship, UMKM, and UKM assistance to people in need.